2020
DOI: 10.3390/medicina56120677
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Disorders in Patients with Newly Diagnosed Pancreatic Adenocarcinoma

Abstract: Background and objectives: Cancer coagulopathy is thought to be partially due to the up-regulation of tissue factor (TF), thrombin-antithrombin complex (TAT) and soluble P-selectin (sP-selectin). The purpose of this study was to evaluate the clinical significance of TF, TAT and sP-selectin in patients with pancreatic cancer. Materials and methods: The study included 93 subjects: 73 newly diagnosed patients with pancreatic adenocarcinoma (42 with stage I-III and 31 with metastatic cancer (stage IV)) and a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Several studies have reported that disease groups, such as cancer, bacterial, and viral infections, and cardiovascular diseases had increased levels of TF-like antigen measured by Imubind [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] ] or Quantikine [ 46 , 58 , 59 ] compared with healthy controls ( Table ). These studies report statistically significant increases in TF-like antigen in different disease groups using the Imubind and Quantikine ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that disease groups, such as cancer, bacterial, and viral infections, and cardiovascular diseases had increased levels of TF-like antigen measured by Imubind [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] ] or Quantikine [ 46 , 58 , 59 ] compared with healthy controls ( Table ). These studies report statistically significant increases in TF-like antigen in different disease groups using the Imubind and Quantikine ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…As in other malignant tumors, some CC parameters have been reported to have diagnostic value for PC. The serum FIB level in patients with PC was significantly higher than that in healthy controls, and the FIB level in metastatic PC patients was further increased [ 28 ]; compared to patients with low-risk intraductal papillary mucinous neoplasms (IPMN), those with high-risk IPMN had a markedly elevated level of FIB [ 29 ]; most PC patients suffered from abnormal coagulation alteration at the time of diagnosis, and tissue factor (TF) and thrombin–antithrombin (TAT) had potential roles in differentiating metastatic PC [ 30 ]. Similar to previous studies, this study also found that some CC indicators, namely, APTT, FIB, and DD2, were abnormally altered in patients with PC compared with patients with BPD; among them, FIB and DD2 could efficiently differentiate PC and EPC according the ROC results.…”
Section: Discussionmentioning
confidence: 99%
“…There are several commercial human TF ELISAs, including IMUNBIND TF ELISA, Sekisui Diagnostics; ZYMUTEST TF ELISA, Aniara Diagnostics; Human TF ELISA, ab108903 Abcam Inc; Quantikine ELISA, R&D Systems. These ELISAs have been used by different investigators to measure levels of TF protein in plasma samples [16,[70][71][72][73][74][75][76][77][78][79][80]. We prepare plasma from untreated and lipopolysaccharidetreated whole human blood samples to generated negative and positive controls, respectively, for TFþ EVs.…”
Section: Measurement Of Tf Protein In Plasma By Elisamentioning
confidence: 99%